Eye drop emulsion containing 0.1% cyclosporin (1 mg/mL) for the treatment of severe vernal keratoconjunctivitis: an evidence-based review and place in therapy - Nebbioso M (Dove Medical Press, 2019)
Marcella Nebbioso, Ludovico Alisi, Francesca Giovannetti, Marta Armentano, Alessandro LambiaseDepartment of Sense Organs, Faculty of Medicine and Odontology, Umberto I Policlinic, Sapienza University of Rome, Rome 00185, ItalyAbstract: Vernal keratoconjunctivitis (VKC) is a rare, recurrent and multifactorial ocular disease, which typically flares up during spring and affects especially male children and adolescents. This condition does not usually respond to common treatments with antihistamines or mast cells stabilizers, whereas corticosteroids have effective results. Corticosteroids need to be carefully administered, to avoid adverse effects, mainly the secondary development of glaucoma, cataracts, or infections. Immunosuppressive agents, such as cyclosporin (CyA) or tacrolimus are, therefore, frequently employed in VKC patients. Only the 0.1% CyA (1 mg/mL) concentration has an approved and specific clinical indication for the treatment of VKC and this drug was given the denomination of orphan drug by the European Commission (EU/3/06/360) in 2006. So far, few studies have been conducted to evaluate the efficacy and the side effects of topical 0.1% CyA. Different topical CyA concentrations, ranging from 0.05% to 2%, and various types of formulation are available at the moment. In the future, 0.1% CyA will presumably take an important part in the management of VKC. The present review focuses on eye drops containing 0.1% CyA; however, more studies will be needed to define its long-term efficacy in the natural course of this severe ocular disease.Keywords: atopy, conjunctivitis, cyclosporin, keratitis, ocular inflammation, vernal keratoconjunctivitis